Bronchial Artery Embolization - Kaufman, Claire S.; Kwan, Sharon W. (Seminars in Interventional Radiology, 2022)
Massive hemoptysis is a highly morbid medical condition with up to 75% mortality with conservative treatment. Bronchial artery embolization has emerged as the common treatment for both acute massive hemoptysis and chronic hemoptysis. This article will review the clinical presentation, bronchial artery anatomy, embolization procedure, complications, and expected outcomes.
Keywords: bronchial artery embolization; embolization; hemoptysis; interventional radiology